2016
DOI: 10.1002/lary.26138
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of vocal fold scarring by local application of basic fibroblast growth factor in a rat vocal fold injury model

Abstract: N/A. Laryngoscope, 2016 127:E67-E74, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Ideally, such biomaterial additives would induce local myofibroblasts to take on a “normal” VFF phenotype and promote pro‐inflammatory MΦ to alter their polarization toward an anti‐inflammatory/pro‐tissue healing phenotype. A growing body of literature indicates that basic fibroblast growth factor (bFGF) has direct anti‐fibrotic effects on VFF and indirect anti‐inflammatory effects . Specifically, VFF treated with bFGF have consistently shown reduced expression of α smooth muscle actin (a marker generally associated with a myofibroblast phenotype) and increased expression of MMP‐1 and hyaluronic acid synthase 2 (markers generally associated with an anti‐fibrotic phenotype) .…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, such biomaterial additives would induce local myofibroblasts to take on a “normal” VFF phenotype and promote pro‐inflammatory MΦ to alter their polarization toward an anti‐inflammatory/pro‐tissue healing phenotype. A growing body of literature indicates that basic fibroblast growth factor (bFGF) has direct anti‐fibrotic effects on VFF and indirect anti‐inflammatory effects . Specifically, VFF treated with bFGF have consistently shown reduced expression of α smooth muscle actin (a marker generally associated with a myofibroblast phenotype) and increased expression of MMP‐1 and hyaluronic acid synthase 2 (markers generally associated with an anti‐fibrotic phenotype) .…”
Section: Introductionmentioning
confidence: 99%
“…They did not find any significant differences when comparing the treated group with the group receiving saline [15]. In another study, basic fibroblast growth factor was shown to reduce vocal cord scar formation [16]. Hirano et al found increased viscoelastic properties and less scar tissue formation after Hepatocyte Growth Factor injection [8].…”
Section: Discussionmentioning
confidence: 97%
“…The use of bFGF to improve vocal fold scarring has been thoroughly investigated 333435363738. The first injection into an atrophic human vocal fold was described in 2008 34.…”
Section: Regenerative Medicine Advances In Oto-hnsmentioning
confidence: 99%